“Poetry Is Not a Luxury”: Why We Should Include Poetry In the Writing Classroom - Nicole Warwick (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
How can poetry transform academic writing’s “masculine” ways of knowing and communicating into transnational exploration?